An unusual case of systemic lupus erythematosus with isolated hypoglossal nerve palsy, fulminant acute pneumonitis, and pulmonary amyloidosis. Issue 3 (March 1989) - Chan, C N; Li, E; Lai, F M; Pang, J A
Abstract : A 53 year old Chinese man with systemic lupus erythematosus (SLE) had an isolated 12th nerve palsy and acute pneumonitis. He died of respiratory failure despite intensive treatment. A limited necropsy was performed, and amyloid deposits were identified in both lung and kidney tissue. This case is highly unusual because (a) to our knowledge an isolated hypoglossal nerve palsy associated with active SLE has never been reported; (b) only one of nine reported cases of amyloidosis in patients with SLE had amyloid deposits in the lung.